Prevalence of Upper Abdominal Complaints in Patients Who Have Undergone Partial Gastrectomy - RJLF Loffeld (Canadian Journal of Gastroenterology)
Little is known about the long term occurrence and prevalence of upper abdominal complaints after previous partial gastrectomy. Therefore, a retrospective, uncontrolled, cross-sectional, descriptive, clinical, endoscopic study was done. A questionnaire was mailed to patients who had undergone partial gastrectomy and been sent for upper gastrointestinal endoscopy. Eight questions were scored on a five-point Likert scale, and a symptom score was calculated. During the five-year study period, 189 patients (137 men, 52 women) were identified as having had a partial gastrectomy -- 143 (76%) received the Billroth II operation and 46 (24%) received the Billroth I operation. The questionnaire was mailed to 124 patients, of whom 79 (64%) responded. Eighty-eight per cent of patients had undergone surgery more than 15 years earlier. Fifty-nine patients (75%) suffered from upper abdominal symptoms. Regurgitation of food, retrosternal heartburn and bile reflux occurred significantly more often in patients who underwent the Billroth II operation. The mean symptom score of patients who underwent Billroth I resection was significantly lower (4.5 [SD 3.6]) than that of patients who underwent Billroth II resection (7.1 [SD 4.4])(P=0.04). One or more symptoms indicative of dumping were found in 70% of patients who underwent Billroth II resection and in 59% of patients who underwent Billroth I resection (not significant). Many patients who had undergone a partial gastrectomy developed upper abdominal symptoms during long term follow-up that were not specifically linked to dumping.